2022
DOI: 10.3390/agriculture12040467
|View full text |Cite
|
Sign up to set email alerts
|

Does a Soybean Intercrop Increase Nodule Number, N Uptake and Grain Yield of the Followed Main Crop Soybean?

Abstract: It is not known whether seed inoculated soybean intercropping can increase the number of nodules, nitrogen uptake and yield of the subsequent main crop, soybean. For this reason, the soybean intercropping approach, sole or mixed cropping with buckwheat, was adopted to examine the influence of inoculation and intercropping of soybean and buckwheat on the subsequent main crop, soybean. Field trials were conducted from 2016 to 2019 in Germany and Poland. For this purpose, soils on which soybeans had not been grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Not all of the root nodules formed were effective in fixing N. Root nodules that were small in size and spread over the roots of branches were relatively ineffective in fixing N. More nodules will increase N content and leaf chlorophyll. Root nodule' amount and N content have a strong correlation [8]. But too high N content reduces chlorophyll content [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all of the root nodules formed were effective in fixing N. Root nodules that were small in size and spread over the roots of branches were relatively ineffective in fixing N. More nodules will increase N content and leaf chlorophyll. Root nodule' amount and N content have a strong correlation [8]. But too high N content reduces chlorophyll content [3].…”
Section: Discussionmentioning
confidence: 99%
“…Soybean plants planted on land that has never been planted with soybeans will produce a small number of root nodules compared to soybeans planted on land that is often planted with legumes. The root nodules' amount can be increased by inoculation of N-fixing bacteria [8]. The soil for research every year in the dry season is always planted with soybeans and the results of the study show that the number of nodules is relatively small (fig.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable response of crops to organic fertiliser in this region has been documented (Imoloame and Ahmed, 2018). Likewise, a study conducted by Porte et al (2022) has reported the favourable response of subsequent crops to the residual effects of the organic fertiliser applied to a previous crop. However, the sole use of organic fertilisers is not viable due to the large quantities required to satisfy crop nutrient demand.…”
Section: Introductionmentioning
confidence: 90%
“…The application of inorganic fertilisers provides nutrients instantaneously to the crops (Ohyama et al, 2017;Díaz-Chuquizuta et al, 2022). Despite the high cost of inorganic fertilisers, they have minimal effects on the subsequent crops (Porte et al, 2022), while their frequent application leads to soil acidification and soil organic matter reduction, thus threatening soil health (Mumbach et al, 2019). The favourable response of crops to organic fertiliser in this region has been documented (Imoloame and Ahmed, 2018).…”
Section: Introductionmentioning
confidence: 99%